Detection of quasi-periodic micro-structure in three millisecond pulsars with the Large European Array for Pulsars. Issue 3 (27th April 2022) - Liu, K; Antoniadis, J; Bassa, C G; Chen, S; Cognard, I; Gaikwad, M; Hu, H; Jang, J; Janssen, G H; Karuppusamy, R; Kramer, M; Lee, K J; et al.
ABSTRACT: We report on the detection of quasi-periodic micro-structure in three millisecond pulsars (MSPs), PSRs J1022+1001, J2145−0750, and J1744−1134, using high time resolution data acquired with the Large European Array for Pulsars at a radio frequency of 1.4 GHz. The occurrence rate of quasi-periodic micro-structure is consistent among pulses with different peak flux densities. Using an auto-correlation analysis, we measure the periodicity and width of the micro-structure in these three pulsars. The detected micro-structure from PSRs J1022+1001 and J1744−1134 is often highly linearly polarized. In PSR J1022+1001, the linear polarization position angles of micro-structure pulses are in general flat with a small degree of variation. Using these results, we further examine the frequency and rotational period dependency of micro-structure properties established in previous work, along with the angular beaming and temporal modulation models that explain the appearance of micro-structure. We also discuss a possible link of micro-structure to the properties of some of the recently discovered fast radio bursts which exhibit a very similar emission morphology.